Strengthening Occupational Health and Safety (OHS) in Schools to Minimize Risks for Students, Teachers, and Visitors: Policy Recommendation - Pertiwi, Wiwik Eko; Denny, Hanifa Maher; Setyaningsih, Yuliani; Laksono, Agung Dwi (Journal of Indonesian Health Policy and Administration, 2025)
Vocational schools equip students with practical skills and expose them to industry-related hazards, making Occupational Health and Safety (OHS) a crucial aspect of the school environment. This study aims to identify key factors behind the weak implementation of OHS in vocational schools. A literature review used articles published between 2017–2024 from national and international journals. The review found poor OHS implementation stems from lack of awareness, inadequate policies, insufficient infrastructure, weak safety culture, and negligence in accident prevention. To address these issues, the study recommends OHS education and training, improvement of school infrastructure, curriculum integration, formation of safety teams, and routine monitoring. These strategies aim to foster a safety-oriented school culture and reduce accident risks for students, teachers, and visitors.